2005
DOI: 10.1037/h0087468
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating Stimulus-Stimulus and Response-Response Effects in the Stroop Task.

Abstract: The separate semantic and response competition interactions between colour and word processing in a manual Stroop task were evaluated by comparing three trial types. Identity trials are both semantically compatible and response compatible (e.g., BLUE in the colour blue), different response trials are both semantically incompatible and response incompatible (e.g., BLUE in the colour green, where blue and green have different response keys), and same response trials are semantically incompatible and response com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 29 publications
(67 reference statements)
8
87
5
Order By: Relevance
“…This finding illuminates an inherent difference between contingency and Stroop effects. In the Stroop literature, both stimulus-stimulus effects (semantic association) and response-response effects (behavioural control) have been observed in the Stroop task (e.g., Schmidt & Cheesman, 2005, 2006Risko, Schmidt, & Besner, in press). In contrast, only behavioural control effects were observed for the contingency task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding illuminates an inherent difference between contingency and Stroop effects. In the Stroop literature, both stimulus-stimulus effects (semantic association) and response-response effects (behavioural control) have been observed in the Stroop task (e.g., Schmidt & Cheesman, 2005, 2006Risko, Schmidt, & Besner, in press). In contrast, only behavioural control effects were observed for the contingency task.…”
Section: Discussionmentioning
confidence: 99%
“…The semantic association and stimulus familiarity accounts both posit that the effect emerges as a result of stimulus interactions (i.e., the learning of associations and the learning of frequency of event pairs, respectively). To help discriminate between these accounts we used a manipulation conceptually similar to that used by De Houwer (2003) and Schmidt and Cheesman (2005) in the Stroop paradigm. Specifically, for each participant, two colours were assigned to a left response key (e.g., blue and green) and two other colours were assigned to a right response key (e.g., yellow and orange).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, there has been a renewed interest in the semantic Stroop effect (SSE; e.g., Augustinova & Ferrand, 2012, 2014Augustinova, Flaudias, & Ferrand, 2010;Augustinova, Silvert, Ferrand, Llorca, & Flaudias, 2015;Labuschagne & Besner, 2015;Manwell, Roberts, & Besner, 2004;Risko, Schmidt, & Besner, 2006;Schmidt & Cheesman, 2005). The semantic manipulation consists of color-associated words (e.g., the word sky, associated with …”
Section: The Semantic Stroop Effectmentioning
confidence: 99%
“…In a properly designed Stroop task, each word should be presented equally often in each colour (unfortunately, this is rarely the case; see Schmidt & Besner, 2008 for a discussion of why this is a problem). Instead, conflict paradigms such as the Stroop task are based on over-trained relations that are partially semantic in nature (e.g., De Houwer, 2003;Risko, Schmidt, & Besner, 2006;Schmidt & Cheesman, 2005). Although some may argue that colour words have an inherent contingency built into them (i.e., because the word BLUE is semantically related to the colour blue and the blue response), it is doubtful that a semantic relationship is the same thing as a contingency, especially since Schmidt et al (2007, Experiment 4) demonstrated that the contingency effect is purely response based, not semantic.…”
Section: Relation To Past Researchmentioning
confidence: 99%